Visual Intelligence - Wang, Yaonan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Anchored in images and graphics, Visual Intelligence focuses on research areas that link visual information processing with intelligence, emphasizing their integration, and on research areas that are experiencing significant advances in the field of visual intelligence. Suggested topics include but are not limited to: Coding and Compression Enhancement and Restoration Image & Video Interpretation and Understanding Image & Video Synthesis, Rendering, Editing, and Visualization 3D Computer Vision and Scene Understanding Visual Intelligence in Neuroscience Machine Learning for Vision Autonomous Systems and Robotics Medical Image Analysis Remote Sensing and Geospatial Analysis Large Models in Visual Intelligence Vision in Quantum Computing Privacy and Security in Visual Systems Other Emerging Technologies Related to Visual Intelligence The journal welcomes reviews, research articles, and perspectives concerning the above topics. .
Keywords: Computer science; Artificial intelligence; Computer Science; Artificial Intelligence